CULTURAL CONTENT ANALYSIS OF HORNBILL TEXTBOOK IN ENGLISH FOR CLASS XI AT CATHEDRAL SR. SEC. SCHOOL LUCKNOW - NOVIA, SINTA (JETA (Journal of English Teaching and Applied Linguistic), 2023)
Abstract: This research explores the cultural content of English textbook for senior high school grade XI entitled “Hornbill Textbook in English for Class XI”. The study aims to investigate what cultures are represented and how cultures are represented in the textbook. To analyse the textbook, this study applied content analysis with descriptive qualitative method. This research used four kinds of instrument in collecting the data; they were textbook, observation, deep reading, and secondary resources. This research also adopted two frameworks from Cortazzi and Jin (3) about types of culture and framework from Adaskou, Britten and Fahsi (1990) about Sense of culture. The analysis of the textbook has revealed some significant results. In comparison to three types of culture, Hornbill Textbook in English for Class XI (Core Course) emphasized Source Culture the most than Target Culture and International Culture. On the other hand, the research finds that cultures are represented by sociological sense (15 times), pragmatic sense (15 times), aesthetic sense (11 times), and semantic sense (10 times).